Monitoring Spatial Growth of Educational Institution using GIS: A Focus on Federal University of Technology Akure, Nigeria - Oyinloye, Michael Ajide (American Journal of Humanities and Social Sciences, 2013)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] --> Land use/ land cover changes is an important components in understanding the interaction of human activities with its environment, therefore it is necessary to analyze such change. The land use/landcover dynamics of Federal University of Technology Akure(FUTA) for a period of sixteen years was analyzed using Multi-temporal and Multi-source image of LandSat (TM) of 1986, LandSat (ETM+) of 2002and Quick bird satellite image of 2012. Maximum likelihood (MAL) supervised digital image classification method was employed using ILWIS 3.2 and Arcview 3.1 GIS software. Eight landcover/landuse classes were created: Built up area, Dense forest, Bareland, Exposed soil, Forest reserves, Gulley forest, Light forest and Rock-out crop. Change information was derived by comparing the classified maps. The results showed that the landcover in the study area has changed during the periods especially the built-up area has increased rapidly for the periods ( 1986- 2012).The results also show increase the bareland, exposed rock out crops while forest reserves, gulley forest and light forest decrease between the same periods. Based on exponential growth formulae, the future prediction of the landuse and landcover change and its subsequent development was modeled between 2012 and 2032.These results could help in providing information for decision and planning purpose and also provide management strategies initiatives that are crucial for such expansion in the study area. <span style="font-size: 10.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->